Structural masonry walls exposed to high temperatures with thermal expansion control - Menegon, Julia; Graeff, Ángela Gaio; Silva Filho, Luiz Carlos Pinto (Revista ALCONPAT, 2019)
This study evaluates the behavior of small clay hollow-bricks walls exposed to high temperatures. Blocks measuring 14 and 19 cm thick were used, with strengths of 7 and 10 MPa. The thickness of the joints, the mortar, and the coating influence was evaluated. The temperatures of the furnace, the interior and the surface of the walls, the expansion of the blocks and the crushing of the joints were measured. It was possible to infer that the samples presented good performance, maintaining their integrity, thermal insulation, and load-bearing capacity. The restriction of the boundaries did not cause the spalling of the blocks, however, it was possible to observe the stress transfer to them in samples with rigid joint mortar. The masonry measuring 19 cm wide and the ones with coating showed better thermal performance.